The Potential of Ethanol Extract Kebar Grass (Biophytum petersianum Klotzsch) in Repairing Rat (Rattus norvegicus) Liver That Exposed to Cigarette Smoke - Mitha Olivia Tjiang; Adrien Jems Akiles Unitly (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2020)
Kebar grass (Biophytum petersianum Klotzsch) is a plant that contains antioxidants, vitamins, and flavonoids which are thought to be able to improve rat liver due to exposure to cigarette smoke. The purpose of this study was to determine the potential of giving ethanol extract of Kebar grass (Biophytum petersianum Klotzsch) in repairing liver damage in rats exposed to cigarette smoke. This study used an experimental method using a completely randomized design (CRD) consisting of four treatments and each of which was repeated three times. The negative group mice were fed normally, the positive control group was the rats exposed to cigarette smoke for 28 days, the first dose the rats that had been exposed to cigarette smoke for 28 days were given ethanol extract of Kebar grass dose of 0.067 mg / head / day for 28 days and at a dose The two rats that had been exposed to cigarette smoke for 28 days were given ethanol extract of grass kebar dose of 0.135 mg / head / day for 28 days. Observation of rat liver was observed under a microscope using Hematoxylin Eosin (HE) staining and histological photomicrographs of the rat liver were analyzed descriptively by displaying histological images. The results showed that the ethanol extract of Kebar grass (Biophytum petersianum Klotzsch) was able to repair rat liver damage (Rattus norvegicus) including inflammatory cells, hydropic degeneration, fat degeneration, and necrosis due to exposure to cigarette smoke.